Upstream. Upper Intermediate B2+: Student's Book - Obee B. Bob (Newbury, Express Publishing, 2010)
Upstream Upper Intermediate B2+ is a modular secondary-level course for learners of the English language at upper-intermediate level. The series combines active English learning with a variety of lively topics presented in themed units. Key Features theme-based units from a wide variety of authentic sources in five modulesa variety of cross-cultural topics systematic development of all four language skills through realistic challenging tasks which encourage the learner's personal engagement lexical exercises practising and activating all essential vocabulary including collocations, idioms and fixed phrases, prepositions, phrasal verbs and word formationa variety of authentic stimulating reading and listening tasks a wide range of speaking activities realistic, stimulating dialogues featuring people in everyday situations grammar sections covering all major grammatical areas plus a Grammar Reference Section composition analysis and practice on all types of writing with full modelsexam and study skills tips Everyday English sections Culture Clips Literature pages Further practice section on Use of English Components Student's Book Teacher's Book brkbook ass audio CDs Test Booklet